Take that, Charlie Chaplin! The meaning of names in J.D. Salinger's PRETTY MOUTH AND GREEN MY EYES. Issue 1 (2nd January 2019) - Weaver, Brett
Abstract: The meaning of the three names in J.D. Salinger's "Pretty Mouth and Green My Eyes" are examined in relation to the author's real-life romance with Oona O'Neill.